2013
DOI: 10.14400/jdpm.2013.11.11.421
|View full text |Cite
|
Sign up to set email alerts
|

Disk Cache Manager based on Minix3 Microkernel : Design and Implementation

Abstract: Disk Cache Manager(DCM), a functional server of microkernel based, to improve the I/O power of shared disks is designed and implemented in this work. DCM interfaces other different servers with message passing through ports by serving as a system actor the multi-thread mode on the Minix3 micro-kernel. DCM proposed in this paper uses the shared disk logically as a Seven Disk and Sodd Disk to enable parallel I/O. DCM enables the efficient placement of disk data because it raises disk cache hit-ratio by increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Citrus peel not only remove hazardous substances, such as antioxidant activity, but prevent circulatory diseases, anti-allergic, anti-bacterial, antiviral, and lipid-lowering effect, immune functioning, and capillaries mineralization have been reported. Chi et al [6], for antibacterial effects of extracts, Park et al [7], for the fermentation extract's antioxidant effects and increased enzyme activity of the citrus peel, Eun et al [8], for the effects in immune cell regulation to the mouse using the citrus peel and Jung et al [9], for the anti-arthritic effects using the citrus peel have been reported. Also the citrus peel contains a large amount of functional substances such as flavonoid, alkolid, lignin, monoterpenoid, sesquiterpenoid and triterpenoid having a high research value.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus peel not only remove hazardous substances, such as antioxidant activity, but prevent circulatory diseases, anti-allergic, anti-bacterial, antiviral, and lipid-lowering effect, immune functioning, and capillaries mineralization have been reported. Chi et al [6], for antibacterial effects of extracts, Park et al [7], for the fermentation extract's antioxidant effects and increased enzyme activity of the citrus peel, Eun et al [8], for the effects in immune cell regulation to the mouse using the citrus peel and Jung et al [9], for the anti-arthritic effects using the citrus peel have been reported. Also the citrus peel contains a large amount of functional substances such as flavonoid, alkolid, lignin, monoterpenoid, sesquiterpenoid and triterpenoid having a high research value.…”
Section: Introductionmentioning
confidence: 99%